Does permanent income determine the vote? - Jo Thori Lind (University of Oslo, Department of Economics, 2004)
I study to what extent voters are forward looking and how future income affects the voting decision. Particularly, I estimate the effect of both transitory and permanent income on preferences for different parties using a panel data set from the Norwegian Election Study. To construct a proxy for permanent income, I use stated expectations about the future economic situation and an estimate of how this affects future income. It turns out that once we include the proxy for permanent income, transitory income has no explanatory power on voting behaviour, supporting the hypothesis of forward looking voting. As expected, a high expected permanent income leads to Conservative voting and a low income to Socialist voting.
Keywords: C25; D31; D72; D91; H11; H53; 330; Voting; permanent income; redistribution; Wahlverhalten; Einkommenshypothese